WOMEN’S EMPOWERMENT THROUGH CANVAS BUSINESS MODEL - Ida Hindarsah (Universitas Pasundan, 2018)
Increasing population in a country, especially in developing countries, has an impact on various aspects, one of them is social impact. The emergence of criminality, acts of violence, sexual harassment is phenomenon which is part of a development, including violence against women who experienced a significant increase. This condition raises high fears so that one way is equipped with self-defense (martial arts). This study aims to comprehensively review women empowerment through the approach of canvas business model. The research method used is qualitative. Data analysis techniques using the steps of reduction, data presentation, conclusion / verification. Testing the validity of data is done through credibility, perseverance, triangulation, feedback / feedback, member check. The result of this research is the existence of Canvas business model on the empowerment of women, this model is made in an effort to develop the existence of WSDK community in the future, in this research also known constraints in the empowerment of women through the approach of canvas business model and describe efforts to anticipate these constraints.